การประกันคุณภาพภายในสถานศึกษาของโรงเรียนเอกชนขนาดเล็ก สังกัดสำนักงานการศึกษาเอกชนจังหวัดปัตตานี - สะอะ ตัสนีม; เก้าเอี้ยน จรุณี; ทวีสันทนีนุกูล เสาวนิตย์ (Al-HIKMAH Journal, 2021)
The objectives of the research were 1) to study the level of the Internal Educational Quality Assurance of Small Private Schools under The Office of Private Education Pattani Province, 2) to compare the level of the Internal Educational Quality Assurance of Small Private Schools under The Office of Private Education Pattani Province. Classified by gender, educational level, and working experience 3) to gather the problems and suggestions of to study the level of the Internal Educational Quality Assurance of Small Private Schools under the Office of Private Education Pattani Province. There were 289 persons under the Office of Private Education, Pattani Province. The tools used were 51 questionnaire estimation scales, the confidence level was 0.959. The statistics analysis used were frequency, percentage, mean and standard deviation. t-test, F-test, and the pair mean test were performed by the way of the chef The results of independent study were as follows: 1)The level of the Internal Educational Quality Assurance of Small Private Schools under The Office of Private Education Pattani Province was at a high level 2)Comparison of the Internal Educational Quality Assurance of Small Private Schools under The Office of Private Education Pattani Province Classified by gender, educational level, and working experience were not different.except for the continuous development of quality education was a statistically significant difference at the 0.05 level 3)The problems of the Internal Educational Quality Assurance of Small Private Schools under The Office of Private Education Pattani Province, namely administrators, teachers and school personnel. lack of understanding of guidelines and procedures for quality assurance operations within educational institutions Information management in educational institutions is not systematic and the participation of personnel involved in the implementation of quality assurance in educational institutions was less.The suggestion were that the educational institutions should raise awareness and create awareness by meeting to explain on the guidelines and procedures for educational quality assurance. to be in accordance with the policies and ministerial regulations as prescribed Information management system should be organized. for quality assurance within educational institutions By allowing teachers and personnel involved in all parties to participate in the implementation of the internal educational quality assurance